The BLM-3AB challenge assay: a micronuclei-based method for measuring DNA Repair Capacity - Xu, Xiao-wen; Zhang, Guang-hui; Sun, Yuan; Zheng, Guo-qiao; Gao, Jing; Jiao, Jie; Au, William; Xia, Zhao-lin (European Journal of Oncology and Environmental Health, 2014)
Efficient DNA repair activity is critically important in maintaining genomic integrity and reducing the risk of cancer. Hence, having sensitive DNA repair functional assays can be useful for identifying such abnormality and can be applied to risk prediction and disease prevention. We have developed a version of the challenge assay to measure DNA repair capacity. The assay is based on the cytochalasin B-micronucleus assay, with DNA damage induced by bleomycin and the subsequent DNA repair mechanism inhibited by 3-aminobenzamide. We used the assay to measure the DNA repair capacity of five vinyl chloride-exposed workers, five benzene-exposed workers and five healthy controls. We found that the DNA repair capacity in both vinyl chloride and benzene-exposed populations were higher than the controls, the mean index being 0.12, 0.16 and 0.54, respectively. For each individual, the micronuclei (MN) frequency of the baseline, being treated with bleomycin only and bleomycin + 3-aminobenzamide (BLM-3AB) together increased gradually. These data support the feasibility of the assay. In conclusion, our assay provides a new tool to identify DNA repair capacity of different individuals and may be applied in pathogenic mechanism-related research, especially occupational-related carcinogenesis.